Apud Genus Omne Futurum: Virgil’s Aenid in Contemporary English Translation - Sophia Ly (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2016)
The archetype of classical Roman epic, Virgil’s Aeneid has enjoyed incredible literary attention since its appearance in the first century of the Common Era. More than eighty English translations of the Aeneid have been published since the beginning of the sixteenth century, and the task of the present article is to understand the place of modern-day translations within the context of such a tradition. By juxtaposing the work of contemporary translators Cecil Day Lewis, Allen Mandelbaum, Robert Fitzgerald, Robert Fagles, and Sarah Ruden, it examines the ways in which a translator’s milieu can manifest itself in subtle artefacts that converge to produce a novel reading of the text. What emerges through the course of the analysis is a plurality of interpretations that exposes the dynamic nature of the the Aeneid and accounts in no small part for its continued ability to find new meaning among audiences today.